3D surveynmodelling for damage assessment in rubble-mound breakwaters under oblique wave incidence - Lemos, Rute; Peña, Enrique; Santos, João; Sande, Jose; Figuero, Andreas; Alvarellos, Alberto; Laiño, Emilio; Reis, Maria Teresa; Fortes, Conceição Juana; B. Kerpe, Nils; Coelho, Ricardo (Italian journal of engineering geology and environment, 2020)
<span data-sheets-value=""1":2,"2":"Several authors have proposed guidelines on how to consider the effects of oblique waves on the stability of armour layers of rubble-mound breakwaters. Especially for very oblique waves, for which the increase in stability is the largest, limited data are available. Under the scope of the HYDRALAB+ transnational access project “RODBreak”, experiments were conducted in a tank at the Marienwerder facilities of the Leibnitz University Hannover (LUH), comprising measurements of sea waves, run-up, overtopping and armour layer damage of a rubble-mound breakwater under oblique extreme wave conditions. This paper focuses on the analysis of damage evolution of the breakwater roundhead subject to these conditions, on the novelty of the non-intrusive survey methodologies and on the advance in knowledge on roundhead stability."" data-sheets-userformat=""2":13057,"3":"1":0,"11":0,"12":0,"15":"Arial","16":10">Several authors have proposed guidelines on how to consider the effects of oblique waves on the stability of armour layers of rubble-mound breakwaters. Especially for very oblique waves, for which the increase in stability is the largest, limited data are available. Under the scope of the HYDRALAB+ transnational access project “RODBreak”, experiments were conducted in a tank at the Marienwerder facilities of the Leibnitz University Hannover (LUH), comprising measurements of sea waves, run-up, overtopping and armour layer damage of a rubble-mound breakwater under oblique extreme wave conditions. This paper focuses on the analysis of damage evolution of the breakwater roundhead subject to these conditions, on the novelty of the non-intrusive survey methodologies and on the advance in knowledge on roundhead stability.